Upaya Pelayanan Rehabilitasi Terhadap Penyalahgunaan Napza Di Yayasan Generasi Emas Aceh (GEMA) - Atikah, Nur; Amalia, Wirda (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Narcotics, Psychotropics and Addictive Substances (NAPZA) are substances or drugs derived from plants or other materials that are not related to plants, whether synthetic or semi-synthetic. When someone uses these substances excessively, they will become addicted and find it difficult to stop, so they will want to use them again and abuse them. The impacts that will be felt are functional disorders or dysfunction and damage related to vital organs. and mental disorders that experience prolonged suffering so that they experience death in vain. Efforts are given to drug abusers by taking them to drug rehabilitation places. Rehabilitation is a place of recovery and special care for people who have social problems, especially drug abuse. The aim of this research is to determine the efforts provided by the Aceh Golden Generation Foundation (GEMA) towards drug abuse clients who are undergoing drug rehabilitation services. The type of research used is descriptive qualitative. Data collection uses observation, documentation and interviews. The results of the research conducted showed that drug rehabilitation service efforts at the Aceh Gold Generation Foundation provided services for 6 months. The types of services provided are: social services, medical services, and spiritual services. The flow of service stages at this foundation is screening, assessment, detection, primary program, family counseling, and in-house aftercare.